HIV-1-specific CD8 T cell responses in a pediatric slow progressor infected as a premature neonate. - Chakraborty, R; Gillespie, G; Reinis, M; Rostron, T; Dong, T; Philpott, S; Burger, H; Weiser, B; Peto, T; Rowland-Jones, S (2002)
We describe the long-term survival of an individual infected with HIV-1 during extrauterine life as a premature newborn. In the absence of viral attenuation in the Nef/LTR structure or significant co-receptor polymorphisms, slow progression was associated with the strong HIV-1-specific broadly cross-reactive CD8 T cell responses. HIV-1 infection as early as 25 weeks' gestation may thus results in the development of immune responses that control viral replication and lead to prolonged survival.